Utility of 28S Ribosomal RNA Gene Domains for Molecular Classification and Phylogeny of Rhinonyssid Mites - Susana A. Sánchez-Carrión; Francisco J. Márquez; Manuel de Rojas (Pathogens)
The family Rhinonyssidae includes endoparasitic, blood-feeding mites that are parasitic on birds and that remain largely unstudied despite their potential role as vectors or reservoirs for various pathogens, like other Dermanyssoidea. Traditionally, the taxonomy of the group has been based on morphometric characteristics, which makes identification very difficult in many groups of closely related species. On the other hand, studies on the phylogenetic relationships within this group of mites have been neglected until the early years of the present century. In this study, twelve species belonging to five different species complexes were identified, and domains D1–D3 28S rRNA of each one were sequenced, for the first time, to investigate the sequence variation and its taxonomic implications for phylogenetic inference. Our data indicate that this molecular marker can effectively differentiate between species within the “motacillae”, “sairae”, “pari”, and “hirsti” complexes of the genus Ptilonyssus and the “melloi” and “columbae” complexes of the genus Tinaminyssus. Furthermore, the phylogenetic tree that can be derived from the domain D1–D3 28S rRNA sequences presented in this study is congruent with the current taxonomy of the Rhinonyssidae. This research calls for a reassessment of the taxonomic status of some group of species.